KAJIAN TENTANG POLITIK HUKUM UNDANG-UNDANG NOMOR 13 TAHUN 2012 TENTANG KEISTIMEWAAN DAERAH ISTIMEWA YOGYAKARTA - Suparno*), Dian Putri Pratama, Retno Saraswati, (Diponegoro Law Journal, 2013)
The Indonesian constitutional system has changed much. The case was marked by the presence of four amendments to the 1945 Constitution. The results of the second amendment of the 1945 Constitution, specifically adds a special article about the privileged area. The focus of the research problem lies in how the region is positioned privileged in the state system in Indonesia. Furthermore, the focus of the next issue is about the assessment of the legal policy in Privilege Act Yogyakarta. Legal policy is the policy line of the law to be applied to both with the new law and the replacement of the old law order to achieve the objectives as stated in the 1945 Constitution. The Research with title " A Study of Political Law on Law No. 13 Year 2012 on the Special Features of Yogyakarta with socio-legal research approach" shows that Indonesia in the conception of autonomy regions adopts an asymmetric decentralization, namely by recognizing constitutional legally autonomous region specific and special. The Recognition of Yogyakarta is inseparable from philosophical, sociological and juridical factor. The Privileges of DIY, is covered land as territory, spatial, cultural, institutional of DIY Regional Government and the determination that has lasted from the in time as well as the core features of the inherent DIY privilege. The Determination of Sultan Hamengku Buwono X and Sri Paku Alam IX as governor and deputy governor in the province is at the core of privileges, and supported by more than 50% of the people of Yogyakarta.